Retrospective assessment of the association between co-morbid disease burden and biochemical parameters in hospitalized hypertensive COVID-19 patients: Co-morbid disease burden in hypertensive COVID-19 patients - Kaynak, Çağdaş; Karageçili, Hasan (Journal of Surgery and Medicine, 2022)
Background/Aim: Hypertension (HT) was examined as a risk factor affecting the progression of the 2019 novel coronavirus disease (COVID-19). In COVID-19 patients, it can be found in many co-morbid diseases, along with hypertension. It is not clear whether the co-morbid burden of the disease affects the prognosis in hypertensive COVID-19 patients and which biochemical parameters may be indicative of this. Therefore, this study was designed to determine the effect of co-morbid disease burden on biochemical parameters in hospitalized hypertensive COVID-19 patients. Methods: After receiving approval from the University Ethics Committee, demographic, clinical, radiological, and laboratory data of 250 hospitalized hypertensive COVID-19 patients between May 2020 and Sept 2020 were screened. Patients with missing records and unclear history of hypertension drug use were excluded from the study. A total of 215 patients were included in the study. Patients were divided into four groups according to the co-morbidity status: (1) HT alone (Group HT0), (2) HT+ Diabetes Mellitus (DM) (Group HTDM1), (3) HT+one co-morbidity exclude DM (Group HT2), and (4) HT+at least two co-morbidities (Group HT3). Results: We analyzed the data of 105 female and 110 male patients. Of the 215 patients whose data were evaluated in this study, 15 patients died. Two hundred people were discharged with recovery. The mortality rate was 7%. Of the hypertension patients, 34.9% had DM, 32.6% had coronary artery disease (CAD), 30.2% had chronic obstructive pulmonary disease (COPD), 16.3% had heart failure (HF), 23.3% had chronic kidney failure (CKD), and 9.3% had cerebrovascular disease (CVD). Twenty-five percent were smokers. Urea, creatinine, direct bilirubin (DBil), and Troponin-I values were significantly higher in the Group HT3 compared to the Group HT0, Group HTDM1, and Group HT2 (P < 0.001, P < 0.001, P < 0.001, P = 0.002 respectively). Glomerular filtration rate (GFR) and albümin levels were significantly lower in Group HT3 than in Group HT0, Group HTDM1, and Group HT2 (P < 0.001 and P < 0.001, respectively). The logistic regression model was statistically significant (χ2(7) = 69.088 and P < 0.001); advanced age, decrease in GFR and plateletcrit (PCT) levels, and increase in D-dimer and DBil levels were observed as predictive parameters of mortality in all hospitalized COVID-19 HT patients. Conclusion: We determined that SARS-CoV-2 pneumonia patients with HT plus at least two co-morbidities were more serious than other patient groups in terms of organ damage and biochemical variables. In our study, we observed an increase in urea, creatinine, D-dimer, Dbil, and Troponin-I values and a decrease in GFR and albumin values as the co-morbidity burden increased in hypertensive COVID-19 patients. However, a decrease in GFR and hemogram PCT levels and an increase in D-dimer and DBil levels could be risk factors for mortality.